A descriptive model of the offence chain for imprisoned adult male firesetters (descriptive model of adult male firesetting) - Barnoux, Magali (Legal and criminological psychology, 2015)
Purpose Firesetting has devastating consequences. Although some theoretical efforts have been made to explain firesetting (i.e., a small number of multi- and single-factor theories), little effort has been devoted to understand how deliberate firesetting unfolds across time (i.e., micro or offence chain theories). This research aimed to produce the first descriptive offence chain theory for incarcerated adult male firesetters. Methods Thirty-eight adult male firesetters - recruited from prison establishments in England and Wales - were interviewed about the events, thoughts, and feelings leading up to, surrounding, and immediately following a deliberate incident of firesetting. Results Using grounded theory analysis, the descriptive model of adult male firesetting (DMAF) was developed documenting the cognitive, behavioural, affective, and contextual factors leading to a single incident of deliberate firesetting. Conclusions New information generated from the DMAF is presented and its contributions to the current evidence base are highlighted. Clinical implications, limitations, and future research directions are also discussed.